The Evolution of AIFA Registries to Support Managed Entry Agreements for Orphan Medicinal Products in Italy - Xoxi, Entela; Facey, Karen M; Cicchetti, Americo (Frontiers in Pharmacology, 2021)
Italy has an implemented prominent system of national registries to support Managed Entry Agreements (MEA), monitoring innovative medicinal products (MP) with clinical uncertainties to ensure appropriate use and best value for money. The registries are funded by pharmaceutical companies, but fully governed by the national medicines agency (AIFA). A desk-top analysis was undertaken of data over a 15-year timeframe of all AIFA indication-based registries and associated EMA information. The characteristics of registries were evaluated, comparing orphan MPs vs. all MPs exploring cancer and non-cancer indications. OMP registries' type vs. AIFA innovation status and EMA approval was reviewed. Of the 283 registries, 182 are appropriateness registries (35.2% relate to OMPs, with an almost equal split of cancer vs non-cancer for OMPs and MPs), 35 include financial-based [20% OMPs (2 non-cancer, 5 cancer)] and 60 registries are payment by result agreements [23.3% OMPs (4 non-cancer, 10 cancer)]. Most OMPs (53/88) came through the normal regulatory route. With the strengthening of the system for evaluation of innovation, fewer outcomes-based have been instigated. AIFA has overcome many of the challenges experienced with MEA through developing an integrated national web-based data collection system: the challenge that remains for AIFA is to move from using the system for individual patient decisions about treatment to reviewing the wealth of data it now holds to optimize healthcare.